Eco-Friendly Synthesis, Biological Evaluation, and In Silico Molecular Docking Approach of Some New Quinoline Derivatives as Potential Antioxidant and Antibacterial Agents - El-Saghier, Ahmed M.; El-Naggar, Mohamed; Hussein, Abdel Haleem M.; El-Adasy, Abu-Bakr A.; Olish, M.; Abdelmonsef, Aboubakr H. (Frontiers in Chemistry, 2021)
A new series of chromenoquinoline derivatives 5-12 were efficiently synthesized via one-pot, multicomponent reaction (MCRs) of resorcinol, aromatic aldehyde, ethyl cyanoacetate and ammonium acetate under solvent free condition. All products were obtained in excellent yield, pure at low cost processing and short time. The structures of all compounds were characterized by spectral and elemental analysis. In addition, all the synthesized compounds 5-12 were screened for their antibacterial and antioxidant activities. Moreover, in silico molecular docking studies of the newly chromenoquinoline derivatives 5-12 with the target enzymes 1DXO and 1AJ6 were achieved to endorse their binding affinities and to understand ligand-enzyme possible intermolecular interactions. The compound 9 was found to have the highest negative binding energy of -9.1 and -9.3 kcal/mol for 1DXO and 1AJ6, respectively. Therefore, compound 9 could be promising chemical scaffold for the development of future drug candidates as antioxidant and antibacterial agents.